1979
DOI: 10.1007/bf01917893
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the mechanism of action of the carotenoid crocetin

Abstract: The carotenoid crocetin was found to be taken up by normal rat muscle cells grown in vitro, and was found in the ribosomal-microsomal fraction, supporting the hypothesis that crocetin affects cell division enzymatic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The hepatoprotective effects of crocetin, as a major Chinese herbal medicine, against oxidative damages in rats have been demonstrated earlier [34]. Crocetin has antioxidant properties by increasing the oxygen transport in plasma, tissues, and cells [35]. Therefore, saffron can protect against oxidative damages due to its major constituent, crocetin.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatoprotective effects of crocetin, as a major Chinese herbal medicine, against oxidative damages in rats have been demonstrated earlier [34]. Crocetin has antioxidant properties by increasing the oxygen transport in plasma, tissues, and cells [35]. Therefore, saffron can protect against oxidative damages due to its major constituent, crocetin.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the only difference is the strain levels at the transition to the different stages; the transitions in the compression tests occur at highest strain levels. Nonetheless, different studies confirmed that skin under compression is highly viscoelastic and shows a nonlinear and time-dependent mechanical behavior [63][64][65][66].…”
Section: Compression Testingmentioning
confidence: 99%